Study conditions for Serbian students in Vienna - Sljukic, Marica; Stojšin, Snežana; Vidicki, Vladan (Sociološki pregled, 2024)
The text is dedicated to the analysis of the conditions in which Serbian students live and study in Austrian capital, and it is based on the results of the empirical research carried out in 2021/2022. The sample consisted of the students of Serbian origin from Serbia, Bosnia and Herzegovina, other former Yugoslav republics, as well as those born in other European countries and are of Serbian origin. The data were collected using an electronic questionnaire and focus group interview. The examination of study conditions included the following parameters: tuition, food and housing costs; methods of financing; the necessity of additional work engagement; financial availability of cultural content; quality of communication at the university and support of students’ organizations. The analysis finds that during their studies at Viennese universities Serbian students are limited by several factors, which have been identified and explicitly stated.
Keywords: Serbian students; Vienna; ethnicity; study conditions; living conditions